Groundwater geochemistry and hydrogeochemical processes in the Lower Ganges-Brahmaputra-Meghna River Basin areas, Bangladesh - Refat Nasher, N.M.; Humayan Ahmed, Md (Journal of Asian Earth Sciences: X, 2021)
•Alkalinity and cation concentrations are higher in the Ganges-Padma basin.•Silicate dissolutions are higher in The Ganges-Padma river basin.•Carbonate dissolutions are major processes in Jamuna-Brahmaputra basin. Groundwater geochemistry and hydrogeochemical processeswere investigated from three different river basins in Bangladesh. The data were collected from BGS website. Total 113 groundwater water samples (10–274 m depth) from different locations of the Ganges-Brahmaputra-Meghna (GBM) river basins of Bangladesh were analyzed to know the diverse groundwater geochemistry and hydrogeochemical processes. GroundwaterCa2+, Mg2+, Na+, K+, Zn2+, Cl−, HCO3–, and SO42− concentrations were consideration for the investigations. The rank of major cations of The Ganges, Brahmaputra, and Meghna basins are Ca2+ > Mg2+ > Na+ > Zn2+ > K+, Ca2+ > Na+ > Mg2+ > K+, and K+ > Mg2+ > Zn2+ > Na+ > Ca2+, respectively. The rank of major anions of The Ganges, Brahmaputra, and Meghna basins are Cl− > SO42− >  HCO3–, Cl− >  HCO3– >  SO42−HCO3– > Cl−>, respectively. The investigations were carried out usingbivariate plot interpretation and factor analysis. Silicate weathering, ion exchange, and seawater intrusion are the dominant processes except carbonate weathering in the Ganges basin. Carbonate weathering is dominant in the Brahmaputra and the Meghna basins. Silicate weathering and gypsum weathering are also present in the Brahmaputra and Meghnabasin’s aquifers to some extent. The Cl− over SO42− indicated anthropogenic influences into groundwater for all three basins.